Improving of Water Quality Parameters Using Stepped Cascade Aerator - Al-janabi, Mohammed A.; Al-Baidhhani, Jabbar H. (Al-Nahrain Journal for Engineering Sciences, 2025)
Hydraulic structures, including cascade aerators, may be acknowledged as important components in improving aeration efficiency because of the intense turbulent mixing combined with large air bubble entrapment at these structures. The main objective of the present study is to achieve maximum aeration efficiency and enhance the concentration of dissolved oxygen in the water since this is an important factor in improving water quality. The present study aims to determine the most proper geometric and dynamic parameters of a typical square-shaped stepped cascade with a total height of 120 cm, and sex steps. A tread of each step is 10 cm and a rise of each step is 20 cm, where aeration efficiency is maximized. The results of the study revealed that the maximum value of water aeration efficiency, meaning an increase in dissolved oxygen in the water using a stepped cascade aerator happened when flow rates of 15 L/min, 25 L/min, and 35 L/min with aeration efficiencies of 22%, 37%, and 42% respectively. Finally, the optimization of flow rates in aeration systems can lead to improved water quality parameters. The most important feature of the present study is the innovation of a natural method of water treatment that relies on the principle of mixing, coagulation, and flocculation by hydraulic methods, which works to reduce the costs of operation.